2006
DOI: 10.1111/j.1467-8624.2006.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Child Bookreading in Low‐Income Families: Correlates and Outcomes During the First Three Years of Life

Abstract: About half of 2,581 low-income mothers reported reading daily to their children. At 14 months, the odds of reading daily increased by the child being firstborn or female. At 24 and 36 months, these odds increased by maternal verbal ability or education and by the child being firstborn or of Early Head Start status. White mothers read more than did Hispanic or African American mothers. For English-speaking children, concurrent reading was associated with vocabulary and comprehension at 14 months, and with vocab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
389
5
14

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(442 citation statements)
references
References 48 publications
24
389
5
14
Order By: Relevance
“…However, research conducted to date suggests that Latino parents are less likely than European Americans to become involved in certain kinds of supportive activities with their children. For example, Latino parents are significantly less likely to read to their young children than are European American parents (Bradley et al 2001;Raikes et al 2006). To a large extent, this pattern may be a function of language barriers, low levels of schooling, and lack of knowledge about American education among Latino immigrants (Cooper et al 1999;García Coll et al 2002).…”
Section: High Parental Expectations Foster Parental Involvement In Scmentioning
confidence: 98%
“…However, research conducted to date suggests that Latino parents are less likely than European Americans to become involved in certain kinds of supportive activities with their children. For example, Latino parents are significantly less likely to read to their young children than are European American parents (Bradley et al 2001;Raikes et al 2006). To a large extent, this pattern may be a function of language barriers, low levels of schooling, and lack of knowledge about American education among Latino immigrants (Cooper et al 1999;García Coll et al 2002).…”
Section: High Parental Expectations Foster Parental Involvement In Scmentioning
confidence: 98%
“…17 Book reading encourages maternal-child interaction and is associated with later cognitive and language development. 18 We selected 2 simple picture books so mothers could talk about the pictures and hoped that mothers would be encouraged to continue with other books. Puzzles build several skills related to the perception of shapes as well as task orientation, persistence, and attention.…”
Section: Figurementioning
confidence: 99%
“…The evidence suggests that it what Raikes et al (2006) refer to as 'concurrent reading' that is important and that regular experience of this links strongly with children's language development, and thence their reading development. A more recent meta-analysis (Mol et al, 2009) has confirmed that interactions between parents and children focused upon books and stories appear to be a key stimulus for children's vocabulary development and their knowledge of print and its conventions.…”
Section: Discussionmentioning
confidence: 99%